C9orf72 Hexanucleotide Expansions Are Associated with Altered Endoplasmic Reticulum Calcium Homeostasis and Stress Granule Formation in Induced Pluripotent Stem Cell-Derived Neurons from Patients with Amyotrophic Lateral Sclerosis and Frontotemporal Dementia. (4th May 2016) - Dafinca, Ruxandra; Scaber, Jakub; Ababneh, Nida'a; Lalic, Tatjana; Weir, Gregory; Christian, Helen; Vowles, Jane; Douglas, Andrew G.L.; Fletcher-Jones, Alexandra; Browne, Cathy; Nakanishi, Mahito; Turner, Martin R.; et al.
Abstract: An expanded hexanucleotide repeat in a noncoding region of the C9orf72 gene is a major cause of amyotrophic lateral sclerosis (ALS), accounting for up to 40% of familial cases and 7% of sporadic ALS in European populations. We have generated induced pluripotent stem cells (iPSCs) from fibroblasts of patients carrying C9orf72 hexanucleotide expansions, differentiated these to functional motor and cortical neurons, and performed an extensive phenotypic characterization. In C9orf72 iPSC-derived motor neurons, decreased cell survival is correlated with dysfunction in Ca 2+ homeostasis, reduced levels of the antiapoptotic protein Bcl-2, increased endoplasmic reticulum (ER) stress, and reduced mitochondrial membrane potential. Furthermore, C9orf72 motor neurons, and also cortical neurons, show evidence of abnormal protein aggregation and stress granule formation. This study is an extensive characterization of iPSC-derived motor neurons as cellular models of ALS carrying C9orf72 hexanucleotide repeats, which describes a novel pathogenic link between C9orf72 mutations, dysregulation of calcium signaling, and altered proteostasis and provides a potential pharmacological target for the treatment of ALS and the related neurodegenerative disease frontotemporal dementia. Abstract : This study presents a comprehensive characterization of cellular pathways that are contributing to cell death in iPSC-derived motor and cortical neurons from ALS/FTD patients carrying pathogenic hexanucleotide repeats in the C9orf72 gene. The apoptotic pathway that we identified in the C9orf72 neurons involves ER calcium elevation and stress, followed by mitochondrial alterations, the release of cytochrome c from the mitochondria and cleavage of caspase-3. Aggregates positive for p62 were detected in these neurons along with high frequency of stress granules, indicating altered proteostatis in the C9orf72 motor and cortical neurons.